The Influence of Service Quality and Atmosphere Store on Customer Satisfaction in Oxygen Caffe in Cirebon City - Sulistiono; Rizky Triono Wijayanto; Yulius Akbar Rajaza; Listatin Hernidatiatin (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to examine and ascertain how customer satisfaction at the Oxygen Coffee shop in Cirebon is impacted by store atmosphere and service quality. This kind of research employs quantitative techniques and is descriptive. The participants in this study were patrons of oxygen coffee shops. Using a Likert scale, a questionnaire instrument, and non-probability sampling with purposive sampling, 96 respondents made up the sample. With the use of the data analysis tool SPSS 25, which facilitates data analysis through the use of multiple linear regression, instrument, and classical assumption tests. The study's findings indicate that while store atmosphere (X2) has a positive and substantial impact on customer satisfaction (Y), service quality (X1) has a positive and significant impact on substantial impact on client satisfaction (Y). Simultaneously influencing customer satisfaction (Y) are the variables of store atmosphere (X2) and service quality (X1).